« Uscio e bottega » : dal Teatro de Los Sentidos a una poetica originale (Itinera, 2017)
This work focuses on the Italian theatrical performance Uscio e bottega by Francesca Giaconi and Lorenzo Bianchi, from its origin - rooted in Theatre of Senses by Enrique Vargas - to the achievement of its own poetics. In this historical period of great changes for dramatic arts, the experience of this little company and their play reflects the ongoing metamorphosis whilst aiming at touching the intimate depth of individuals. This work retraces the steps that lead to the creation of this theatrical performance, stressing its unique and original elements as well as those influenced by the Theatre of Senses. We will discuss the special participation of the public and the traces of a regionalism so peculiar as to make Uscio e Bottega a noteworthy specimen in the rich, albeit somehow jagged, Italian theatrical landscape.